2018
DOI: 10.1523/eneuro.0267-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Rapid Cell Signaling Mechanisms Underlying the Memory-Enhancing Effects of 17β-Estradiol

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 69 publications
(164 reference statements)
7
62
2
Order By: Relevance
“…In the hippocampus of females, 17β-estradiol (E2) is thought to mediate object recognition memory via phosphorylation of the cell signaling kinase extracellular signal-related kinase (ERK) (Fan et al 2010;Fernandez et al 2008;Kuroki et al 2000;Pereira et al 2014). In the hippocampus of males, E2 does not increase ERK phosphorylation and increases in phosphorylated ERK in the hippocampus are not necessary for memory enhancements following E2 treatment (Koss et al 2018). While there is a body of literature examining the role of estrogen in the hippocampus on object memory, the role of sex hormones in the perirhinal cortex is not as well defined.…”
Section: Discussionmentioning
confidence: 99%
“…In the hippocampus of females, 17β-estradiol (E2) is thought to mediate object recognition memory via phosphorylation of the cell signaling kinase extracellular signal-related kinase (ERK) (Fan et al 2010;Fernandez et al 2008;Kuroki et al 2000;Pereira et al 2014). In the hippocampus of males, E2 does not increase ERK phosphorylation and increases in phosphorylated ERK in the hippocampus are not necessary for memory enhancements following E2 treatment (Koss et al 2018). While there is a body of literature examining the role of estrogen in the hippocampus on object memory, the role of sex hormones in the perirhinal cortex is not as well defined.…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in the distribution of ERs (Bourque et al, 2011), together with a different role of ER subtypes in brain plasticity, neuroprotection and repair in male and female neurons (Bryant and Dorsa, 2010; may participate in the generation of sex differences in the neuroprotective actions of estradiol. In addition, there are differences in ER signaling in the brain of males and females (Tabatadze et al, 2015;Oberlander and Woolley, 2016;Koss et al, 2018;Jain et al, 2019;Meitzen et al, 2019;Zafer et al, 2019), which are in part mediated by epigenetic modifications in ER encoding genes (Schwarz et al, 2010;Giatti et al, 2018) and micro RNAs (Giatti et al, 2018) and are also dependent on sexually differentiated interactions with the signaling mechanisms of other neuroprotective factors, such as BDNF (Scharfman and MacLusky, 2014), IGF-1 (Munive et al, 2016) or the endocannabinoid system (Tabatadze et al, 2015), which in turn also present sex differences in the brain. All these sexually differentiated molecular mechanisms cause different responses to estradiol in the brain of male and female animals (Tabatadze et al, 2015;Munive et al, 2016;Koss et al, 2018) and may determine sex differences in the neuroprotective actions of the hormone.…”
Section: Participation Of Estrogen Signaling In the Generation Of Sexmentioning
confidence: 99%
“…Several studies have reported that differences between male and female rats in evoked AMPAR/NMDAR signaling in hippocampal synapses, along with differences in the magnitude of evoked LTP, may underlie sex differences in spatial memory (Monfort et al, 2015;Qi et al, 2016). Estrous has been shown to modulate diffusion of AMPARs to the surface in female mice (Palomero-Gallagher et al, 2003;Tada et al, 2015;Bechard et al, 2018), which may underlie part of the reported importance of estrogenic mechanisms for memory in females (Cordeira et al, 2018;Frick et al, 2018;Koss et al, 2018;Wang et al, 2018;Koebele et al, 2019). However, the sex-specific role of AMPARs in memory may also be specific to the type of memory task being tested, as a study by Dachtler et al concluded that the GluA1 subunit was necessary only for male, not female, mice in fear conditioning memory, but that hippocampal GluA1 was necessary for spatial learning in both sexes (Dachtler et al, 2011).…”
Section: Discussionmentioning
confidence: 99%